2011
DOI: 10.4314/gmj.v44i2.68884
|View full text |Cite
|
Sign up to set email alerts
|

Resistance-mediating polymorphisms of <i>Plasmodium falciparum</i> among isolates from children with severe malaria in Kumasi, Ghana

Abstract: SUMMARYBackground: Antimalarial drug resistance has been a major contributor to the failure of the battle against malaria in many developing countries. The P. falciparum genes, pfcrt and pfmdr-1, have been implicated in chloroquine resistance. The objective of this study was to determine the presence of mutant alleles of these chloroquine resistance genes among isolates of P. falciparum from children presenting with severe malaria in Ghana. Methods: Venous blood samples were taken from patients, and plasma chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Various studies since the change in malaria treatment policy in Ghana have reported different levels in prevalence of the mutant pfcrt T76 in P. falciparum isolates collected from different parts of the country [ 4 , 5 , 16 ]. CQ pressure is driven by high CQ usage in an area and it is a major determinant of selection and spread of CQ resistance genes among P. falciparum population [ 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies since the change in malaria treatment policy in Ghana have reported different levels in prevalence of the mutant pfcrt T76 in P. falciparum isolates collected from different parts of the country [ 4 , 5 , 16 ]. CQ pressure is driven by high CQ usage in an area and it is a major determinant of selection and spread of CQ resistance genes among P. falciparum population [ 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Abruquah and colleagues had reported 88.6% K76T prevalence in Kumasi [4], while Kwansa-Bentum and colleagues reported 51.6% K76T prevalence in southern part of Ghana [5]. A study conducted in 2004 by Duah and colleagues reported different T76 mutations among the various sentinel sites for their studies [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent World Health Malaria Report estimated about 241 million malaria cases and 627,000 deaths, and 95% of the cases and deaths are from sub-Saharan Africa (WHO, 2021). As a result of the growing threat of parasite and vector resistance to antimalarial drug and insecticides (Abruquah et al, 2010; Adams et al, 2018; Alam et al, 2011; Awolola et al, 2018; Diallo et al, 2022; Fukuda et al, 2021; Hawkes et al, 2015; Oboh et al, 2018; Patel et al, 2017; Straimer et al, 2022; Tacoli et al, 2016; Traoré et al, 2019; Tumwebaze et al, 2021), attention is now focused, more than ever on other control measures that can be deployed for malaria control. Unfortunately, vaccine development has also not been spared from parasite evasive mechanisms.…”
Section: Introductionmentioning
confidence: 99%